Small Non-Coding RNAs in the Human Placenta: Regulatory Roles and Clinical Utility - Telkar, Nikita; Stewart, Greg L.; Pewarchuk, Michelle E.; Cohn, David E.; Robinson, Wendy P.; Lam, Wan L. (Frontiers in Genetics, 2022)
The placenta is a vital organ formed during pregnancy, and being the interface between the mother and fetus, it is paramount that placental functioning is strictly controlled. Gene expression in the placenta is finely tuned - with aberrant expression causing placental pathologies and inducing stress on both mother and fetus. Gene regulation is brought upon by several mechanisms, and small non-coding RNAs (sncRNAs) have recently been appreciated for their contribution in gene repression. Their dysregulation has been implicated in a range of somatic and inherited disorders, highlighting their importance in maintaining healthy organ function. Their specific roles within the placenta, however, are not well understood, and require further exploration. To this end, we summarize the mechanisms of microRNAs (miRNAs), Piwi-interacting RNAs (piRNAs), small nuclear RNAs (snRNAs), small nucleolar RNAs (snoRNAs), and transfer RNAs (tRNAs), their known contributions to human placental health and disease, the relevance of sncRNAs as promising biomarkers throughout pregnancy, and the current challenges faced by placental sncRNA studies.